Turkey - Transport Sector Expenditure Review : Synthesis Report - World Bank (Washington, DC, 2013)
Turkey is an upper-middle income country with a population of 73 million. It has a diversified economy with a strategic geographical position, located on the southeastern side of Europe and southwestern side of Asia. Continued economic growth, combined with increases in the urban population, will place increasing demands on Turkey's transport infrastructure. High middle income countries such as Turkey typically see very rapid increases in demand for transport services for several decades. Consequently public expenditures on transport sector have increased substantially in Turkey in recent years. Public expenditures on transport have almost doubled from 1.06 percent of Gross Domestic Product (GDP) in 2004 to 1.92 percent in 2010, and the transport sector accounted for the bulk of the increase in total public investments over this period. Turkey's transport sector has been growing both in terms of its size and the quality of the network, and currently compares well with similar middle income countries. However, Turkey's infrastructure quality lags behind the levels of EU countries, particularly in the railroads and ports sector. The need for transport infrastructure improvements is also reinforced by the results of business surveys.